The influence of Orientalism on the curriculum of higher Education - Sharma, Yak Raj (Journal of Musikot Campus, 2025)
Eastern philosophy is a very traditionalist philosophy. Eastern philosophies are Hindu, Buddhist, Charvaka, Jain, Himalayan and Tibetan philosophies. In today's time, it is mandatory to study Eastern Philosophy. Which shows the terrible situation that will come tomorrow in human behavior. Studying Eastern philosophy means assessing the situation that will appear in tomorrow's society. What is the impact of Eastern philosophy on the curriculum of higher education? What is the opinion of the stakeholders regarding Eastern philosophy? Why is it necessary to implement Eastern philosophy in higher education curriculum? Such problems have been investigated. This study is limited to professors teaching at the campus level, students and parents. The study uses tools such as unstructured interview questionnaires, classroom observation forms, and focus group discussions. The data has been analyzed using a qualitative method. Convenient, circular and purposeful sample selection methods have been used in the study. A small part is included. The perspective of teachers and students who are teaching and studying Eastern philosophy has been influenced by Eastern philosophy. Eastern philosophy should be implemented from school level to higher education. Which has brought negativity in human behavior. Since Eastern philosophy is a religion-based idea, its influence has been on human behavior. Eastern philosophies have a huge influence on the intellectual, emotional, spiritual and physical aspects of people today. Due to the Eastern philosophy, prayers are being performed in houses, temples and religious places. Humility, positive thinking, respect for elders and love for children have been developed in the students. They have morals, discipline, duty and faith in God. Students from poor families are leaving their inclination towards traditional Hinduism and are increasingly leaning towards other religions. Stakeholders should include a compulsory curriculum of Eastern philosophy in secondary and higher education.